2016
DOI: 10.1097/gox.0000000000001044
|View full text |Cite
|
Sign up to set email alerts
|

The Lesser Palatine Nerve Innervates the Levator Veli Palatini Muscle

Abstract: Summary:When the lesser palatine nerve (LPN) is supposed to be a branch of the trigeminal nerve and innervate sensation of the soft palate, whether the LPN contains motor fibers is unclear. In this study, we monitored the electromyogram of the levator veli palatini (LVP) muscle on stimulating the LPN during palatoplasty in 3 patients. The electromyogram of the muscles showed the myogenic potential induced by electrostimulation of the LPN. Taken together with the finding from our previous anatomical study that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…or the extent of sinusitis (analyzing each specific sinuses) have not been evaluated for the effect on the E-tube function separately. The vidian nerve at the floor of the sphenoid sinus or the lesser palatine nerve passing the wall of the maxillary sinus, for example, can affect the levator palatini muscle influencing E-tube function or cause referred otalgia influencing ETDQ-7 [25,26]. The effect of medications including topical corticosteroids prescribed to the patients and the three excluded cases with persistent sinusitis after ESS also burden the possibility of bias in this study.…”
Section: Discussionmentioning
confidence: 98%
“…or the extent of sinusitis (analyzing each specific sinuses) have not been evaluated for the effect on the E-tube function separately. The vidian nerve at the floor of the sphenoid sinus or the lesser palatine nerve passing the wall of the maxillary sinus, for example, can affect the levator palatini muscle influencing E-tube function or cause referred otalgia influencing ETDQ-7 [25,26]. The effect of medications including topical corticosteroids prescribed to the patients and the three excluded cases with persistent sinusitis after ESS also burden the possibility of bias in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Clinically, some patients with facial palsy have soft palate palsy on the same side (Podvinec, 1952), suggesting that the VII nerve may also contribute motor innervation to the soft palate. Electrical stimulation of the LPN in humans induced LVP activities (Kishimoto, Matsuura, et al, 2016b). In this study, we found that the human LPN on each side gave off four to six branches to supply not only the mucosa and glandular tissue but also the palatal muscles, including the MU, LVP, and PP.…”
Section: Discussionmentioning
confidence: 99%
“…The controversies concerning innervation of the palatal muscles may be attributed, at least in part, to species differences and the methods used. Previous efforts to study the innervation of the human soft palate muscles have relied primarily on traditional anatomical and electrophysiological methods (Boorman & Sommerlad, 1985;Broomhead, 1951;Domenech-Ratto, 1977;Kishimoto, Matsuura, et al, 2016b;Shimokawa et al, 2004Shimokawa et al, , 2005. A particular nerve branch innervating a given muscle might be wrongly identified by gross dissection.…”
Section: Discussionmentioning
confidence: 99%